Cattle parasitosis in the zona da mata region of Minas Gerais state, Brazil I. Seasonal behavior of gastro-intestinal nematodes - Furlong, John; Abreu, Helenisa Gloria Lovisi de; Verneque, Rui da Silva (Pesquisa Agropecuaria Brasileira, 2014)
Two tracer calves were necropsied monthly between October 1980 and September 1982 at Coronel Pacheco, Zona da Mata, State of Minas Gerais, Brazil. Cooperia spp. (80%) and Haemonchus spp. (17%) were the most prevalent genera. The climate of the region proved suitable to the development and surviving of these genera during the year but occurring a significant diminution (P < 0.05) of Haemonchus spp. during the dry season (April to September). The rainfall proved best correlating climatic parameter and monthly nematode index, when compared with hydric balance and bioclimatograph, and was considered the best indicator of the larval availability in the pasture of this region. The dry season is the critical period for calves due to the available larval number and the low forage availability.